2016
DOI: 10.1021/acscatal.5b02752
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric Reduction of Difficult-to-Reduce Ketones: Triple-Code Saturation Mutagenesis of an Alcohol Dehydrogenase

Abstract: Catalytic asymmetric reduction of prochiral ketones with the formation of enantio-pure secondary alcohols is of fundamental importance in organic chemistry, chiral man-made transition-metal catalysts, or organocatalysts and enzymes of the alcohol dehydrogenase (ADH) type. A distinct limitation is the traditional requirement that the αand α′-moieties flanking the carbonyl function differ sterically and/or electronically. Difficultto-reduce ketones such as tetrahydrofuran-3-one and tetrahydrothiofuran-3one and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
102
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(111 citation statements)
references
References 61 publications
3
102
0
6
Order By: Relevance
“…Conformational dynamics‐guided identification of key residues at the binding pocket . Our previous study revealed that residues A85, I86, W110, L294 and C295 are involved in tuning enantioselectivity and activity . We therefore selected them as potential candidates for mutagenesis .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conformational dynamics‐guided identification of key residues at the binding pocket . Our previous study revealed that residues A85, I86, W110, L294 and C295 are involved in tuning enantioselectivity and activity . We therefore selected them as potential candidates for mutagenesis .…”
Section: Resultsmentioning
confidence: 99%
“…Following the reduction mechanism of TbSADH, the carbonyl oxygen of the substrate coordinates to the Zn 2+ and a hydride is supplied from NADPH to the carbonyl carbon atom, and the binding orientation of the substrate with respect to the NADPH determines the stereochemistry of the product . In order to explore the effect of mutation on stereoselectivity at the molecular level, docking and MD calculations were performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, the best way to make such a crucial decision requires two steps: 1) exploratory NNK‐based saturation mutagenesis is performed at individual residues lining the respective binding pocket, requiring the screening of only 94 transformants for 95 % library coverage, and the data is used to identify the influence of specific amino‐acid exchange events at hotspots; 2) on the basis of this information, a triple code is chosen that is then used to randomize a multiresidue site composed of all or parts of the hotspots. This strategy was applied successfully to the alcohol dehydrogenase (ADH) from Thermoanaerobacter brockii (TbSADH) as the catalyst in the enantioselective transformation of “difficult‐to‐reduce” prochiral ketones and to cytochrome P450‐BM3 as the catalyst for the regio‐ and stereoselective oxidative hydroxylation in cascade reactions …”
Section: Introductionmentioning
confidence: 99%
“…Compared with chemical synthesis, biocatalytic route has become a subject of considerable interest due to its high chemo-, regio-, and enantioselectivities, and mild reaction conditions and environmental benignity (Lalonde 2016;Ni and Xu 2012;Wohlgemuth 2010). In recent years, enzymatic asymmetric reduction of prochiral ketones for preparation of optically active alcohols has gained increasing favor (Nakamura et al 2003;Nealon et al 2015;Noey et al 2015;Sun et al 2016;Wang et al 2011).…”
mentioning
confidence: 99%